Compte rendu de l’exposition « Cityscapes in Anime Background Art » - Delphine Vomscheid (Ebisu: Études Japonaises)
From 17 June to 19 November 2023, an exhibition entitled “Cityscapes in Anime Background Art” was held at the Kanazawa Museum of Architecture. On show were more than 140 graphic documents relating to six Japanese science-fiction animated films released between 1980 and 2000: Akira, Patlabor, Patlabor 2, Ghost in the Shell, Metropolis and Tekkonkinkreet. These illustrations, which come in a variety of types and formats, all stem from the process of designing the urban and architectural environment. Displayed as objects in their own right, devoid of characters, they highlight the considerable work put in by the artists in the creation of these cities. These creations are so intricate that we can consider them “doubles” of the Japanese city – sometimes inspired by reality, sometimes by dystopia.